The Impact Of Pornography Addiction On Interpersonal Communication Capability (A Case Study In Students Of Islamic Education Faculty Ibn Khaldun Bogor University) - Tauhid, Muhammad; Rahman, Imas Kania; Rofiah, Rofiah (KOMUNIKA, 2018)
The purpose of this study was 1) to find out and explain fornography, 2) To find out and explain interpersonal communication, 3) to determine the impact of fornographic addiction on interpersonal communication of FAI students at Ibn Khaldun University, Bogor. This type of research is field research (field research), which is data collection carried out by research at the scene of the symptoms being investigated. Methodologically this research is descriptive qualitative, namely research that produces descriptive data in the form of written or oral words from people and observed behavior. The results showed 1) pornography addiction types of FAI students at Ibn Khaldun University in Bogor, namely in the form of prono films, and pornographic images that are often seen and downloaded via smartphone, 2) Interpersonal communication of University of Ibn Khaldun FAI students found communication barriers such as not saying what he is feeling. Most students tend to be closed either to their friends or other people especially with the opposite sex, 3) Addiction to pornography has an impact on interpersonal communication of FAI students atIbn Khaldun University, Bogor. Pornography makes students' thinking become full of sex. Sex thoughts will master theirsubconscious. This will make people mentally disturbed and challenged to try.